Effectiveness of Strategy Instruction Using Podcasts in Second Language Listening and Speaking - Kang, Tingting (ProQuest LLC, 2016)
Mobile devices have become a significant part of students' lives. The average number of hours that college students reported using their smartphones each day was nine hours--more than half of their daily waking hours (Roberts, Yaya, & Manolis, 2014). Although software developers and teachers have started to develop and incorporate various mobile applications to promote teaching and learning, as Egan wrote, "the best of technology does not by itself create a productive learning environment" (1999, p. 281). Applying suitable and effective instructional techniques in mobile-assisted language learning (MALL) is crucial. Podcasts, one type of MALL, have been proposed as a technological tool to improve second language (L2) learners' listening and speaking skills (e.g., Ducate & Lomicka, 2009; O'Bryan & Hegelheimer, 2009). Such improvement might be achieved by using teaching methods that include self-regulated listening and self-awareness strategies in order to guide students toward autonomous learning (e.g., Alderson, 2005; Roussel, 2011). This dissertation study evaluated the effectiveness of incorporating self-regulated and awareness strategies with podcast activities in an integrated listening and speaking English as a second language (ESL) class. Participants were 20 intermediate ESL learners enrolled in an intensive English program (IEP) at a southwestern American university. The treatment length was 12 weeks. This study employed a quasi-experimental research design. Two independent variables were time (within-subjects factor) and group (between-subjects factor). Six dependent variables included listening skills, speaking skills, attitudes, self-regulation, self-awareness, and use of podcasts. A series of mixed-method comparisons were conducted to analyze two groups' performances on the pre-, post- and delayed post-measures. Additionally, participants' weekly listening logs and speaking performances were charted across weeks to examine trends. Results revealed that (a) both groups improved significantly on listening and speaking achievement tests, (b) no statistical differences were observed between groups on the listening, speaking, and strategy measures, (c) the experimental group's listening comprehension was slightly better and more stable than the comparison group's, (d) the experimental group produced slightly slower and more comprehensible speech, and (e) both groups showed positive attitudes towards the podcast activities. This dissertation study provided empirical research support on the effectiveness of instructional techniques using podcasts, perfected podcast activities in L2 classes, provided important information about students' preference and ownership of different technology devices, and motivated L2 learners to take advantage of authentic materials outside the classroom. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]